Relationship between the intention–behavior gap and self-efficacy for physical activity during childhood. (March 2019) - Isa, Tsunenori; Ueda, Yuya; Nakamura, Ryo; Misu, Shogo; Ono, Rei
This study investigated the relationship of a gap between the intent to be physically active and actual participation in physical activity ('intention–behavior gap') and self-efficacy for physical activity during childhood. A self-report questionnaire was used to collect information from 946 children from the fourth and sixth grades in Japan on self-efficacy, intention, and physical activity. Children with an intention–behavior gap (high intent–low activity or low intent–high activity) had higher self-efficacy scores than those with low intent and low activity (27.66 or 27.65 vs. 21.69; p < .001). They had lower self-efficacy scores than those with high intent and high activity (27.66 or 27.65 vs. 30.56; p < .001). Children with an intention–behavior gap had lower self-efficacy for physical activity than those who intended to be and were physically active. Such children may benefit from education interventions that focus on improving self-efficacy.